2013
DOI: 10.1002/ldr.2235
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Annual and Perennial Herbaceous Species for the Rehabilitation of a Sand Quarry in a Mediterranean Environment

Abstract: Commercial seeds are widely used for re‐vegetation interventions in Mediterranean areas. These seeds mostly consist of species and varieties of non‐local provenance. The current practice relies mainly on forage or turf and fast growing species, even if it is often inefficient. Twenty‐two local populations or commercial varieties of annual and perennial species belonging to the botanical families Leguminosae, Graminaceae and Compositae were evaluated in a 4‐year field experiment in order to investigate their po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The need to redirect subsidies to the support of sensible management alternatives that might render these systems more sustainable in the future is also a recurrent recommendation (Beaufoy et al, 1994;Caballero et al, 2007). A good example is the improvement of self-sown legume-based pastures, which constitutes a long-term lowering cost strategy (Porqueddu, 2007) and an opportunity for the rehabilitation of degraded land (Porqueddu et al, 2013). This recommendation could be of use for farm types where pasture efficiency was not at its best, for example, in the case of extensive sheep farmers in Centro (C3) and full-time cattle farmers in Alentejo (A3).…”
Section: Farming Systems and Sustainable Land Management: Rotation Anmentioning
confidence: 99%
“…The need to redirect subsidies to the support of sensible management alternatives that might render these systems more sustainable in the future is also a recurrent recommendation (Beaufoy et al, 1994;Caballero et al, 2007). A good example is the improvement of self-sown legume-based pastures, which constitutes a long-term lowering cost strategy (Porqueddu, 2007) and an opportunity for the rehabilitation of degraded land (Porqueddu et al, 2013). This recommendation could be of use for farm types where pasture efficiency was not at its best, for example, in the case of extensive sheep farmers in Centro (C3) and full-time cattle farmers in Alentejo (A3).…”
Section: Farming Systems and Sustainable Land Management: Rotation Anmentioning
confidence: 99%
“…Analytic‐hierarchy processes have been widely used to select species in the process of postmining vegetation restoration (Soltanmohammadi, Osanloo, & Aghajani, ; Talema et al, ). Native species have proven to be more suitable than non‐native species for vegetation restoration (Conrad & Tischew, ; Porqueddu et al, ). Yuan et al () found that monoculture forests of Robinia pseudoacacia Linn.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there will be a trend to integrate green manure in agricultural system as an alternative strategy for lowering chemical fertilizer usage and restoring a deteriorated field environment. Current research focuses on improving soil physical and biochemical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14], contaminated soil rehabilitation [15][16][17][18][19][20][21][22], improving crop yield [13,[23][24][25][26], development of sustainable agricultural system [27][28][29][30][31][32] at the micro scale. However, developing green manure at a regional scale is especially affected by both human interventions and the natural soil properties.…”
Section: Introductionmentioning
confidence: 99%